Analisis Faktor-Faktor Yang Mempengaruhi Terjadinya Financial Distress Perusahaan Asuransi Umum Syariah di Indonesia - Utama, Septia Sakinah Rizki; Anggraini, Tuti; Harahap, Muhammad Ikhsan (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This study aims to identify whether the factors of liquidity, leverage have a significant influence on financial distress in Islamic General Insurance Companies in Indonesia. This study uses a descriptive method with quantitative data analysis in this research population, namely all General Sharia Insurance Companies in Indonesia in 2020. In this research sample, namely three General Sharia Insurance Companies in Indonesia, using multiple linear regression analysis techniques and processed using the assistance of the IBM SPSS Statistics 26 computer application program. According to the partial fact that liquidity has a significant effect on financial distress. Partially, leverage has a significant effect on financial distress. Simultaneous estimation explains that the financial distress variable is influenced by liquidity and leverage factors simultaneously. Investors and potential investors who are considering investing in the company PT Asuransi Umum Syariah should consider the company's financial condition, such as liquidity and liabilities, which have a significant influence when predicting the situation of a company facing financial difficulties. You need to pay attention to indicators and thus you can minimize your risk namely the risk of loss.